KAJIAN HUKUM ISLAM TERHADAP TRADISI SEDEKAH BUMI (KONVENSI TRADISI JAWA) DALAM PERSPEKTIF FIQIH IMAM SYAFI’I - Daud Rismana; Muhamad Farchan Sulistiyanto (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
Among the people of Java. Especially in the Cangkring Village of Rembang, Karanganyar, Demak. There are various rituals that are sacred and have been hereditary traditions, one of which is the earth alms tradition is a cultural ritual from the past. The community in the Cangkring Rembang Village, Karanganyar, Demak, considers that the real purpose and purpose of the earth alms tradition is a form of gratitude that created the universe namely God who has bestowed agricultural produce for the people in the Cangkring Rembang Village. Therefore, the people of Cangring Village in Rembang always carry out the tradition of alms in the earth, which is in the middle of the moon or dzulqo’dah. In this study included field research in the Cangkring Rembang Village, Karanganyar, Demak. While information is collected by interviews. The data that has been obtained is analyzed using data analysis techniques with descriptive, deductive, and inductive methods. Likewise, almsgiving is a convention of Javanese tradition with Islam. Given the earth alms tradition is a ritual passed down from ancestors to later generations, even though the earth alms tradition does not directly mention it in the Holy Qur'an and the Prophet's Hadith, but it is reviewed from the Islamic law in perspective fiqh, it is still permissible but does not contradict existing Islamic laws, and does not associate partners with Allah SWT.